Yield and soil fertility build up by aromatic grasses on degraded riverbed land of north western Himalayan foothills - Tomar, J.M.S.; Kaushal, R.; Rathore, A.C.; Mandal, D.; Chaturvedi, O.P. (Indian Journal of Agroforestry, 2020)
The study was conducted to investigate the performance on yield and soil fertility accretion of various aromatic grasses under riverbed lands in Doon valley of North Western Himalayas. The rooted slips of three aromatic grasses viz., lemon (Cymbopogon flexuosus), java (C. martini) and palmarosa (C. winterianus) were planted with onset of monsoon in 2009. Results revealed that survival of grasses recorded in the order of lemon grass > java grass > palmarosa grass. Maximum height was recorded in palmarosa grass (1.77 m) followed by lemon (1.26 m) and minimum was recorded in java grass (0.98 m). Biomass yield was maximum in lemon grass (9.94 Mg ha-1) followed by palmarosa (7.09 Mg ha- 1) and java grass (6.27 Mg ha-1). Whereas, maximum oil yield (144.4 kg ha-1) was obtained from lemon grass followed java grass (111.5 kg ha-1) and least with palmarosa (74.4 kg ha-1). Roots study revealed that roots of lemon grass reached up to maximum 102 cm soil depth and extended lateral spread up to 48.0 cm. Soil physico-chemical properties showed significant improvement under lemon grass. Benefit cost ratio after four year of cultivation was 1.95 for lemon, 1.84 for java and 1.65 for palmarosa grass, which revealed that all the grasses were economically viable for the degraded conditions. Based on growth parameters, soil fertility accretion and economic returns, it is concluded that lemon and java grasses have potential to rehabilitate degraded riverbed lands in Doon Valley.